Pengaruh Penghasilan Wajib Pajak, Penerapan E-System Pajak dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Selama Pandemi Covid 19 (Studi Pada Kantor Pelayanan Pajak Pratama Kota Pangkalpinang Tahun 2020–2021) - Harfenas Situmorang; Yunita Maharani (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This study aims to determine the effect of Taxpayer Income, Application Of Tax E-System And Tax Knowledge On Taxpayer Compliance Of Personal Persons During The Covid-19 Pandemic (Study at the Pangkalpinang City Pratama Tax Service Office 2020-2021). This study uses quantitative methods. The population in this study were Individual Taxpayer which registered at KPP Pratama, Pangkalpinang. The sampling was conducted by Simple Random Sampling Method. The number of samples was determined by the researcher purposively with total of sample are 100 Individual Taxpayer. Data sources in this study use primary data with Quantitative Descriptive Method where the data collection were used in this study is survey methods with questionnaires as survey instrument. The data analysis technique used in this study is Multiple Linear Regression analysis tecniques. The results showed that Implementation of Taxpayer Income have a positive and significant effect on the level of Taxpayer Compliance. This is evidenced by the t-value greater than the table (2,591 > 1.984) at significant (0.011 < 0.05). Application Of Tax E-System have a positive and significant effect on the level of Tax Compliance. This is evidenced by the t-value greater than the table (3.371 > 1.984) at significant (0.001 < 0.05). Tax Knowledge have a positive and significant effect on the level of Taxpayer Compliance. This is evidenced by the t-value greater than the table (3,277 > 1.984) with a significant (0.001 < 0.05). Taxpayer Income, Application Of Tax E-System and Tax Knowledge have a positive and significant effect together on the Taxpayer Compliance Level. This is evidenced by the regression coefficient that is positive at 0.279; 0.396; 0.291 and Fcount greater than Ftable (108.501 > 2.70).Keywords: Taxpayer Income, Application Of Tax E- System, Tax Knowledge, Individual Taxpayer Compliance